Maternal and perinatal outcomes of pregnant women with tetralogy of Fallot: a tertiary center experience from south-India. (17th September 2022) - Keepanasseril, Anish; Raj, Ashwini; Plakkal, Nishad; Satheesh, Santhosh; Pillai, Ajith Ananthakrishna; Kundra, Pankaj
Abstract: Background: Women with tetralogy of Fallot especially uncorrected are at increased risk of adverse maternal and perinatal outcomes. Method: We reviewed the maternal complications and pregnancy outcomes of women with tetralogy of Fallot (ToF), having corrected or uncorrected lesion during the period from 2011 to 2019 attending a south-Indian tertiary care center. Data regarding demographics, clinical course, and medications received and echocardiographic diagnosis regarding ToF, labor and delivery details, and postpartum follow-up was collected from the records. For each case, four women matched for age (±2 years), without a diagnosis of heart disease, were included as controls. We compared the outcomes in pregnant women with ToF and controls as well between those who have undergone repair with those without repair and also with the controls. Results: There were 27 pregnancies in 19 patients with ToF, including eight pregnancies in seven women with uncorrected lesions. There was no maternal death or occurrence of infective endocarditis. Women with uncorrected lesion had significantly higher rates of fetal growth restriction (37.5% vs 6.7%), preterm birth (50% vs. 13.3%) resulting in lower birth weight (1907.5 g vs. 2607.3 g)) compared to those with a corrected lesion. Women with corrected lesion had similar outcomes to the controls ( p > .5). Conclusion: Women with uncorrected ToF are at increased risk of perinatal complications compared to those with corrected lesion and require care under a multidisciplinary team, with an individualized plan for delivery to optimize the outcomes.